2003
DOI: 10.1093/aje/kwg107
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from Cancer and Other Causes among Airline Cabin Attendants in Europe: A Collaborative Cohort Study in Eight Countries

Abstract: There is concern about the health effects of exposure to cosmic radiation during air travel. To study the potential health effects of this and occupational exposures, the authors investigated mortality patterns among more than 44,000 airline cabin crew members in Europe. A cohort study was performed in eight European countries, yielding approximately 655,000 person-years of follow-up. Observed numbers of deaths were compared with expected numbers based on national mortality rates. Among female cabin crew, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
75
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 31 publications
8
75
0
2
Order By: Relevance
“…A pooling study on cancer mortality, published in 2003, 14 was carried out in a large cohort of European female flight attendants. The authors reported a reduction in all-site cancer mortality (meta-standardized mortality ratio, meta-SMR 0.78, CI 0.66, 0.95) and a slight but nonsignificant excess in mortality from breast cancer (meta-SMR 1.11, CI 0.82, 1.48).…”
Section: Introduction Fmentioning
confidence: 99%
“…A pooling study on cancer mortality, published in 2003, 14 was carried out in a large cohort of European female flight attendants. The authors reported a reduction in all-site cancer mortality (meta-standardized mortality ratio, meta-SMR 0.78, CI 0.66, 0.95) and a slight but nonsignificant excess in mortality from breast cancer (meta-SMR 1.11, CI 0.82, 1.48).…”
Section: Introduction Fmentioning
confidence: 99%
“…A large pooled analysis of mortality data from several European countries confirmed the increased risks for skin melanoma, but did not observe increases for any other cancer sites. [9][10][11] Flight and cabin crew members have a complicated exposure history because their occupation leads to specific lifestyle characteristics, and these may act as possible confounders to the health effects of occupational hazards. Such lifestyle characteristics include recreational sunlight exposure during rest periods in hot places overseas or leisure activities.…”
mentioning
confidence: 99%
“…Overall the conclusion from Zeeb et al (56) was that among airline cabin crew in Europe, there was no increase in mortality that could be attributed to cosmic radiation or other occupational exposures to any substantial extent.…”
Section: Epidemiologymentioning
confidence: 92%
“…In the study by Zeeb et al (56), the excess mortality from malignant melanoma was restricted to male cabin crew members.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation